PENGARUH LINGKUNGAN KERJA DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI PADA PUSAT PENELITIAN PERKEBUNAN GULA INDONESIA (P3GI) KOTA PASURUAN - Mafiroh, Miftakhul Laila; Sutikno, Bambang; Wahyuni, Hari (Yayasan Education and Social Center, 2025)
The Indonesian Sugar Plantation Research Center, abbreviated as P3GI, is a sugar research institution in Indonesia. Based in Pasuruan, East Java, P3GI is tasked with conducting research, producing studies on sugar and sweetener technology and products for the advancement of the sugar community, especially sugarcane farmers and sugar factories, and providing technical assistance to clients. This study aims to analyze the influence of the work environment and discipline on employee performance at the Indonesian Sugar Plantation Research Center (P3GI) in Pasuruan City. The research method used is quantitative. Data were collected through distributing questionnaires to respondents who are P3GI employees, using a saturated sample of 56 employees of the P3GI office in Pasuruan City. The analysis used includes research instrument testing, descriptive analysis, classical assumption testing and hypothesis testing. Based on the results of the study, the R Square value was 56.4%, which means that employee performance can be explained by 56.4% by the work environment and discipline. Work environment and discipline have a significant effect on employee performance as shown by the calculated F value of 14.39 and the F table value of 3.17 and a significance value of 0.000 <0.05. The work environment has a significant effect on performance as shown by the calculated T value of 3.125 which is greater than R table (2.005) and a significance value of 0.002 <0.05. Discipline has a significant effect on employee performance as shown by the calculated T value of 2.693 which is greater than T table (2.005) and a significance value of 0.009 <0.05.